2019
DOI: 10.4194/1303-2712-v19_11_01
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Despite the potential importance of parasitic nematode, Anguillicoloides crassus for the survival of eel, only a few studies have addressed this issue on eel stocks of Turkey. The current study reports baseline data on prevalence of parasites and pathological status in naturally infected eels from three important river estuaries (Seyhan River, Göksu River and Manavgat River) in Turkey. In total, 70 individuals of Anguilla anguilla from three river estuaries were examined and 46 (65.7%) specimens were infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…According to Moravec and Taraschewski (1988), Anguillicoloides crassus, which started to be found in Europe in the early 1980s, was first reported in Turkey by Genç et al, (2005) in the Ceyhan river. In the following years, different studies have been found in the river systems of the northeastern coasts of the Mediterranean (Genç et al, 2008;Koyuncu et al, 2017;İnnal et al, 2019). However, a limited number of studies have been reported on the Turkish coasts of the Aegean Sea, including Köyceğiz-Dalyan (Çolak et al, 2012), İzmir Bay Çamaltı (Gürkan et al, 2022) and Vistonis Lake (Macnamara et al, 2014;Kantzoura et al, 2021) on the Greek coasts.…”
Section: Discussionmentioning
confidence: 99%
“…According to Moravec and Taraschewski (1988), Anguillicoloides crassus, which started to be found in Europe in the early 1980s, was first reported in Turkey by Genç et al, (2005) in the Ceyhan river. In the following years, different studies have been found in the river systems of the northeastern coasts of the Mediterranean (Genç et al, 2008;Koyuncu et al, 2017;İnnal et al, 2019). However, a limited number of studies have been reported on the Turkish coasts of the Aegean Sea, including Köyceğiz-Dalyan (Çolak et al, 2012), İzmir Bay Çamaltı (Gürkan et al, 2022) and Vistonis Lake (Macnamara et al, 2014;Kantzoura et al, 2021) on the Greek coasts.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies related to this species were done by Başaran and Kelle (1976) and Cantoray and Özcan (1975) in Turkey. Various studies were carried out on this infestation in fish in Turkey (Uzbilek and Yıldız, 2002;İnnal et al, 2007;Demirtaş and Altındağ, 2011;Koyun et al, 2015;Saç et al, 2015) and in the World (Olson et al, 2002;Bouzid et al, 2008a;Hajirostamloo, 2009;Mehraban et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It survives 1–2 days in the water and develops to procercoid larva in copepod. Fish eat the copepod and subsequently, a large plerocercoid larva develops in the body cavity of the fish (İnnal et al., 2007 ). In Iran, the highest overall prevalence of ligulosis was recorded in Chalcalburnus chalcoides (83.08%) (Garedaghi & Mohammadi, 2012 ), Alburnus filippi (81.87%) and Alburnoides biponctatus (80%) (Mortazavi et al., 2005 ) (Table 3 ).…”
Section: Fish‐borne Zoonotic Parasitesmentioning
confidence: 99%